One-pot self-assembly synthesis of Ni-doped ordered mesoporous carbon for quantitative hydrogenation of furfural to furfuryl alcohol. Issue 4 (18th February 2021) - Tang, Yiwei; Qiu, Mo; Yang, Jirui; Shen, Feng; Wang, Xiaoqi; Qi, Xinhua
Abstract : Ni-Doped OMC with high catalytic activity and stability for furfural hydrogenation to furfuryl alcohol was prepared by a one-pot evaporation-induced self-assembly process with biomass-derived gallic acid as carbon precursor and Ni 2+ as crosslinker. Abstract : Ni-Doped ordered mesoporous carbon (Ni@OMC) was prepared by a one-pot solvent evaporation-induced self-assembly (EISA) process with sustainable biomass-derived gallic acid as the carbon precursor, F127 as the soft template and Ni 2+ as the cross-linker and catalytically active ingredient. Ni particles with ca. 7.8 nm diameter were uniformly dispersed in the carbon skeleton of the synthesized OMC due to the confinement effects of Ni particles in the carbon skeleton of OMC by coordination between gallic acid molecules and metal Ni 2+ ions in the EISA process. The as-synthesized Ni@OMC sample showed excellent catalytic performance for the hydrogenation of biomass-derived furfural into furfuryl alcohol (FFA), and a FFA yield as high as 98% could be achieved at 180 °C in 4 h reaction time in 1-propanol solvent in the presence of 3 MPa H2 pressure. The prepared Ni@OMC exhibited good stability and recyclability. This work provides a green and simple one-pot strategy for the synthesis of metal-doped OMCs without using harmful phenolic and formaldehyde compounds, which should have many applications in fields such as catalysis, drug delivery and energy storage.